Emotional Stability of Student-Athletes in Resisting Swearwords as Their Expressive Supports during Sport Competitions - Heny Setyawati; Tandiyo Rahayu; Didik Rinan Sumekto; Nur Haziyanti Binti Mohamad Khalid (Universitas Pendidikan Indonesia, 2023)
Emotional stability, in sports, is a fundamental defense in supporting athlete performance during competitions. This study aimed at investigating the relationship between student-athlete swearing expressions and their emotional performance stability experienced during competitions. This study involved 387 undergraduate student-athletes from Indonesia and Malaysia, including 176 from Indonesia and 211 from Universiti Pendidikan Sultan Idris (UPSI) Malaysia,as respondents.The respondents included 222 (57.4%) males and 165 (42.6%) females. Respondent ages ranged between 17 to 23 years (Mage = 20; SD = 4.24). The student-athlete backgrounds were identified to be amateurs and professional categories in the following sports: badminton, basket, volleyball, athletics, sepak takraw, and kickboxing. Data collection used a self-rated questionnaire constructed in Google Forms through simple random sampling. Data were analyzed using descriptive statistics and Pearson correlations by employing the IBM-SPSS, version 25.0. The findingsshowed that the student-athlete emotional temptations (M = 3.37; SD = 1.189), toughness in managing bad habits (M = 3.31; SD = 1.286), improper words in expressing swearwords(M = 1.85; SD = .932), physical and mental discomfort management (M = 2.85; SD = 1.280), and uncomfortable feeling when expressing the swearwords (M = 2.44; SD = 1.128) ranged from never to frequent category. These determinants influenced a positive and significant contribution on student-athletes’ emotional and physical performance stabilities. This study completed student-athlete rating subjectivity when perceiving their emotional stability.